2015
DOI: 10.1063/1.4914049
|View full text |Cite
|
Sign up to set email alerts
|

Thermo acoustic study of carbon nanotubes in near and far field: Theory, simulation, and experiment

Abstract: Wave propagation of carbon nanotubes embedded in an elastic medium J. Appl. Phys. 97, 044307 (2005); 10.1063/1.1849823Simulation study of carbon nanotube field emission display with under-gate and planar-gate structures Carbon nanotube webs exhibit interesting properties when used as thermo-acoustic projectors. This work studies thermo-acoustic effect of these sound sources both in near and far field regions. Based on two alternative forms of the energy equation, we have developed a straightforward formula for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 19 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…The core of thermal acoustic is the propagation of the heat. SP is decided by the thermal energy diffused into air: 42 …”
Section: Resultsmentioning
confidence: 99%
“…The core of thermal acoustic is the propagation of the heat. SP is decided by the thermal energy diffused into air: 42 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, most of the latest studies focused on the evaluation of the performance enabled by the new materials, often overlooking the physical phenomena underlying TA sound generation. While the full electro-acoustic transduction of TA loudspeakers is widely documented in the literature [ 1 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], the thermal response of TA loudspeakers to the applied electrical stimuli and its role in determining the acoustic response were investigated superficially in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the shutter patterned E‐skin could possess broad application prospects in health monitoring and alarm owning to the optimally overall performance. We have confirmed that there are great differences for SPL based on different patterns, and these results can be explained by the following theoretical formula normalPrms=mair⋅f22CnormalpTnormal0r⋅trueQ˙air where P rms is the root‐mean‐square sound pressure, m air is the molecular weight of air, f is the frequency of the acoustic, C p is the heat capacity under constant pressure, T 0 is the room temperature, r is the distance between the sound source and the microphone, and Q air is the thermal energy diffused into the air.…”
Section: Resultsmentioning
confidence: 99%